2018
DOI: 10.3164/jcbn.17-130
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress and renal injury in patients with sepsis

Abstract: Sepsis remains one of the leading causes of death in intensive care units. The early phase of sepsis is characterized by a massive formation of reactive oxygen and nitrogen species such as superoxide and nitric oxide. However, few comprehensive studies on plasma antioxidants have been reported. Increased oxidative stress was confirmed in sepsis patients (n = 18) at the time of hospitalization by a significant decrease in plasma ascorbic acid and a significant increase in the percentage of oxidized form of coen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…(2) Under acute inflammatory conditions like sepsis, the substantial formation of superoxide and nitric oxide, and their product peroxynitrite, is expected. In fact plasma UA levels declined significantly in patients with sepsis during a stay at an intensive care unit (8) because UA is a good inhibitor of peroxynitrite. (22)(23)(24) However, serum UA levels remained constant in centenarians and 76-year-old controls, suggesting that inflammation in centenarians is moderate and chronic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Under acute inflammatory conditions like sepsis, the substantial formation of superoxide and nitric oxide, and their product peroxynitrite, is expected. In fact plasma UA levels declined significantly in patients with sepsis during a stay at an intensive care unit (8) because UA is a good inhibitor of peroxynitrite. (22)(23)(24) However, serum UA levels remained constant in centenarians and 76-year-old controls, suggesting that inflammation in centenarians is moderate and chronic.…”
Section: Resultsmentioning
confidence: 99%
“…(5)(6)(7) In fact, we observed a decline in plasma antioxidants, namely vitamin E (VE), ubiquinol-10 (CoQ10H 2 ), vitamin C (VC), and uric acid (UA), in patients with sepsis. (8) However, no comprehensive study has been reported for centenarians. In this study, we compared serum levels of antioxidants in centenarians and 76-year-old controls.…”
mentioning
confidence: 99%
“…The redox balance of CoQ10 in the human serum is a good marker of oxidative stress because the reduced form of CoQ10 (ubiquinol) is very sensitive to oxidation and is quantitatively converted to its oxidized form (ubiquinone) [ 42 ]. Actually, elevation of the % CoQ10 was confirmed in patients with various diseases, including sepsis, hepatitis, cirrhosis, hepatoma, Parkinson’s disease, juvenile fibromyalgia, amyotrophic lateral sclerosis (ALS), and post-cardiac arrest syndrome [ 43 ]. Although further studies on the relationship between vegetable intake and the inhibition of CoQ10 oxidation are required, the elevation of plasma concentration of carotenoids may contribute to the improvement of the redox status.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore developed a simple and reliable method for the simultaneous electrochemical detection of plasma CoQ10H 2 and CoQ10 (4) and applied the method to patients with various diseases. Significant increases in %CoQ10 were observed in patients with hepatitis, (5) cirrhosis, (5) hepatoma, (5) juvenile fibromyalgia, (6) amyotrophic lateral sclerosis (ALS), (7) Parkinson disease, (8) post cardiac arrest syndrome, (9) and sepsis (10) as compared to age-matched healthy controls. It is interesting that newborn babies have significantly higher plasma %CoQ10 than adults (11) and %CoQ10 increases with age.…”
Section: Introductionmentioning
confidence: 99%